Surgical Outcomes of Subtotal Parathyroidectomy for Renal Hyperparathyroidism - Min Song Kim (Clinical and Experimental Otorhinolaryngology, 2020)
Objectives The aim of this study was to evaluate the effectiveness of subtotal parathyroidectomy for patients with renal hyperparathyroidism. Methods We studied 25 patients with renal hyperparathyroidism who underwent subtotal parathyroidectomy from October 2002 to October 2017. We analyzed serum intact parathyroid hormone (iPTH), calcium, and inorganic phosphorus levels before and at multiple time points following surgery, and evaluated the surgical outcomes and complications. Results Of the 25 patients, 13 (52%) were male and 12 (48%) were female, and the mean age was 53.4±9.3 years. The mean duration of dialysis before parathyroidectomy was 156.8±79.5 months. Mean preoperative serum iPTH and calcium levels were 1,199.0±571.3 pg/mL and 10.5±1.0 mg/dL, respectively. At 6 months postoperatively, the mean iPTH and calcium levels decreased to 49.2±47.6 pg/mL (P<0.01) and 8.0±1.0 mg/dL (P<0.01), respectively. Recurrent hyperparathyroidism occurred in two patients: one subsequently underwent kidney transplantation and the other continued hemodialysis and maintained normal calcium levels. One patient developed postoperative permanent hypoparathyroidism. Conclusion Subtotal parathyroidectomy is a safe and effective surgical treatment for renal hyperparathyroidism.